Inovasi Bahan Ajar Literasi Berbasis Bermain dalam Meningkatkan Kemampuan Membaca Permulaan Anak TK - Erlinda, Aprilia Arna; Umaya, Nazla Maharani; Harjito, Harjito (Lembaga Teewan Journal Solutions, 2026)
Early reading skills constitute a fundamental literacy competence that forms the basis for children's future academic success. However, literacy instruction in kindergarten frequently faces challenges, including limited engaging teaching materials, teacher-centered practices, and low levels of children's participation. This study aimed to develop play-based literacy teaching materials that are valid, practical, and effective in improving the early reading skills of kindergarten children. A Research and Development (R&D) approach was employed by adapting the Borg and Gall development model, encompassing needs analysis, product planning, development, expert validation, revision, limited field testing, field implementation, and final refinement. Participants included kindergarten teachers and children in Demak Regency, Indonesia. Data were collected through observations, interviews, questionnaires, documentation, and learning outcome assessments, then analyzed using descriptive qualitative and quantitative techniques. The findings demonstrated that the developed materials achieved high validity based on evaluations by subject matter experts, media experts, and practitioners. Implementation significantly improved children's learning motivation, classroom engagement, letter recognition, phonemic awareness, and word-building skills. Additionally, the use of manipulative learning media fostered meaningful learning experiences and encouraged active participation. These findings indicate that play-based literacy materials provide an effective and innovative instructional resource for enhancing early reading skills and strengthening literacy development in early childhood education